In pursuit of non-heme superoxoiron(III) complexes : a bioinspired approach - Lim, Ming Hui (Nanyang Technological University, 2021)
Non-heme enzymes are ubiquitous in nature and can successfully harness dioxygen activation for a large variety of biological reactions. More specifically, the 2-His-1-carboxylate facial triad superfamily of oxygenases has been extensively researched upon and their functions based upon Fe and Mn ions. While the superoxo intermediate has been proposed as the active oxidant in most enzymatic systems, more work is required to fully elucidate and understand how dioxygen can be harnessed in bioinspired catalysis. To this end, synthetic models are used as a means to access the reactivity of these transient species and thereby allow for characterization and comparison against the enzymatic systems. This dissertation explores the synthesis and initial UV-vis spectroscopic studies of the Fe, Mn and Co model complexes based upon a modular ligand framework that would mimic the coordination environment found in non-heme iron oxygenases. Chapter 1 reviews the role of the superoxo species shared among most non-heme enzymatic systems under the 2-His-1- carboxylate facial triad superfamily. The structure and reactivity of the synthetic superoxo-metal complexes are also reported. In Chapter 2, we report a series of five coordinate complexes supported by the pyridine-amine-pyrrole (1-H) tridentate system and an ancillary bidentate ligand (2/3). The structural and electrochemical properties of these complexes are also explored. We then proceed to explore the reactivity of the complexes with dioxygen at low temperatures in Chapter 3, monitored using UV-vis spectroscopy. The data obtained is consistent with expectations of putative superoxo species.